2023
DOI: 10.1111/petr.14498
|View full text |Cite
|
Sign up to set email alerts
|

Donor specific antibody surveillance among pediatric kidney transplant programs: A report from the improving renal outcome collaborative

Abstract: Background Kidney transplantation (KT) is the preferred treatment for children with end‐stage kidney disease. Recent advances in immunosuppression and advances in donor specific antibody (DSA) testing have resulted in prolonged allograft survival; however, standardized approaches for surveillance DSA monitoring and management of de novo (dn) DSA are widely variable among pediatric KT programs. Methods Pediatric transplant nephrologists in the multi‐center Improving Renal Outcomes Collaborative (IROC) participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Some experts suggest that surveillance biopsy after 1 year post‐transplant is of low clinical utility 10 while others report clinically actionable findings on 9%–30% of surveillance biopsies performed at 2 or 3 years for pediatric recipients 11,12 . The UNOS survey found that 3 and 12 months were the most common timepoints for surveillance biopsy among adult transplant programs, 9 and the pediatric Improving Renal Outcomes Collaborative reported that surveillance biopsies were performed at 41.4% of the 29 centers in their study 13 . Under modern immunosuppression practices, Landsberg et al 12 .…”
Section: Surveillance Biopsymentioning
confidence: 99%
See 3 more Smart Citations
“…Some experts suggest that surveillance biopsy after 1 year post‐transplant is of low clinical utility 10 while others report clinically actionable findings on 9%–30% of surveillance biopsies performed at 2 or 3 years for pediatric recipients 11,12 . The UNOS survey found that 3 and 12 months were the most common timepoints for surveillance biopsy among adult transplant programs, 9 and the pediatric Improving Renal Outcomes Collaborative reported that surveillance biopsies were performed at 41.4% of the 29 centers in their study 13 . Under modern immunosuppression practices, Landsberg et al 12 .…”
Section: Surveillance Biopsymentioning
confidence: 99%
“…11,12 The UNOS survey found that 3 and 12 months were the most common timepoints for surveillance biopsy among adult transplant programs, 9 and the pediatric Improving Renal Outcomes Collaborative reported that surveillance biopsies were performed at 41.4% of the 29 centers in their study. 13 Under modern immunosuppression practices, Landsberg et al 12 identified TCR in 20.8% of pediatric kidney transplant recipients undergoing a surveillance biopsy at 3 months post-transplant and 42.9% 6 months post-transplant, the majority of which were borderline rejections, and Seifert et al 14 showed borderline rejection detected on surveillance biopsy prior to 6 months post-transplant was associated with a 5-year composite outcome of acute rejection or allograft failure (aHR 2.89 p < .01).…”
Section: Surveill An Ce B Iopsymentioning
confidence: 99%
See 2 more Smart Citations